A Randomized Double-Blind Sham-Controlled Study of Transcranial Direct Current Stimulation for Treatment-Resistant Major Depression - Blumberger, Daniel; Tran, Lisa; Fitzgerald, Paul; Hoy, Kate; Daskalakis, Zafiris J. (Frontiers in Psychiatry, 2012)
Objectives: Transcranial direct current stimulation (tDCS) has demonstrated some efficacy in treatment-resistant major depression (TRD). The majority of previous controlled studies have used anodal stimulation to the left dorsolateral prefrontal cortex (DLPFC) and a control location such as the supraorbital region for the cathode. Several open-label studies have suggested effectiveness from anodal stimulation to the left DLPFC combined with cathodal stimulation to the right DLPFC. Thus, this study evaluated the efficacy of tDCS using anodal stimulation to the left DLPFC and cathodal stimulation to the right DLPFC compared to sham tDCS. Methods: Subjects between the ages of 18 and 65 were recruited from a tertiary care university hospital. Twenty-four subjects with TRD and a 17-item Hamilton Rating Scale for Depression greater than 21 were randomized to receive tDCS or sham tDCS. The rates of remission were compared between the two treatment groups. Results: The remission rates did not differ significantly between the two groups using an intention to treat analysis. More subjects in the active tDCS group had failed a course of electroconvulsive therapy in the current depressive episode. Side effects did not differ between the two groups and in general the treatment was very well tolerated. Conclusion: Anodal stimulation to the left DLPFC and cathodal stimulation to the right DLPFC was not efficacious in TRD. However, a number of methodological limitations warrant caution in generalizing from this study. Ongoing, controlled studies should provide further clarification on the efficacy of this stimulation configuration in TRD. ClinicalTrials.gov Identifier: NCT01078948.